Fabrication of cadmium sulfide and cadmium telluride solar cells and their characterisations - Albalushi, Abdulkarem (2014)
The thin film CdTe based solar cells have the potential for high efficiency and have been investigated for 40 years due to their variations in flexibility in manufacturing technology, rapid deposition, and an excellent match to the solar spectrum. Cadmium Telluride (CdTe) is a promising thin film photovoltaic (PV) material due to its near ideal bandgap of ? 1.5 eV and its high optical absorption coefficient. The typical CdTe thin film solar cell was a substrate configured with a window layer (CdS). The gold (Au) was used as an absorber (CdTe) and a back contact. Both semiconductor films, CdS and CdTe, were deposited by high vacuum evaporation at room temperature, and deposited on glass substrates with fluorine doped tin oxide (FTO) front contact. The back contact was made to enhance carriers flow from CdTe layer to the electrode. The structure and morphology of the prepared cells were determined by X-ray diffraction (XRD), Energy Dispersive X-ray (EDX) top views and Field Emission Scanning Electron Microscopy (FESEM) cross-section. The XRD of the prepared films showed a polycrystalline of cadium sulphide and cadium telluride structure with peaks at 2? = 26.54o and 23.71o, respectively. It was found that the distance between the created particles (d) is 3.34 Å for CdS, and 3.6 Å for CdTe. The FESEM image showed clearly the layers of fabricated cell and the junction between N-type and P-type was a visible from cross-section. The efficiency of cells was investigated by using three different thicknesses of CdS and CdTe. Efficiency about 7.98 %, Ics = 19.1 mA and Voc = 0.76 V were achieved by deposited thin layer of CdS and thick layer of CdTe with a gold as a back contact